EFEK PAPARAN DEKOK BIJI PINANG (Areca catechu) TERHADAP MOTILITAS SPERMATOZOA TIKUS (Rattus norvegicus): UPAYA MENEMUKAN KANDIDAT ANTIFERTILITAS PRIA (The Effect of Betel Nut Extract (Areca catechu) on Mice Spermatozoa Motility (Rattus norvegicus: Effort to Find Out Man Antifertility Candidate) - Akmal, Muslim (Jurnal Kedokteran Hewan, 2008)
This research was conducted to prove the ability of betel nut extract (Areca catechu) in causingdegradation of sperm motility on rats (Rattus norvegicus) strain Wistar. This research used 2-3 monthsage, 200-250 g body weight of male white rats Rattus norvegicus strain Wistar. The rats were dividedinto 5 groups in equal number, 3 rats each group. They were a control group without treatment and 4treatment groups which were given different doses of betel nut extract for 7 days, i.e., 1, 2, 3, and 4 g/200g body weight respectively. The result showed that increasing doses of betel nut extract can result indegradation of sperm motility significantly (P0.05).Keywords: Areca catechu, Rattus norvegicus, sperm motility